A percepção da atuação da área de gestão de pessoas das empresas privadas e organizações governamentais nos estados de Minas Gerais, Rio de Janeiro e São Paulo segundo os profissionais das demais áreas funcionais - Garcia, Adriana Amadeu (2006)
In the past there were many lawyers working in the human resources area, nowadays it doesn't happen anymore, because this area wishes to offer a better service. According to some writers, that strategic service is the ideal way for the organization to achieve its goal. Since there are not many researches about this issue, this dissertation will give a support not only for academic but also for professionals that work in private and public organizations. The goal of this dissertation is to identify how professionals, except for the ones who work in the human resources, realize the actions of the human resources in private and public organizations. Besides, this dissertation also makes a comparison between these two kinds of action. The result of this research is neither good nor bad. The goal of this research was to find problems involved on this issue and better solutions for them.